Pengembangan Modul Praktikum STEAM pada Prodi Pendidikan Islam Anak Usia Dini - Damayanti, Eka; Marjani Alwi, Besse; T, M. Yusuf; Patiung, Dahlia; Nur, Fitriani (NANAEKE: Indonesian Journal of Early Childhood Education, 2025)
The purpose of this study is to develop a STEAM practicum module in the Early Childhood Islamic Education study program. The type of research used in this study is research & development (R&D) to find new knowledge or develop a product. The product produced in this study is the STEAM practicum module. Data analysis uses quantitative techniques. The results of the study include a STEAM-based practicum module in the Early Childhood Islamic Education Study Program (PIAUD) which was developed through the 4D model (Define, Design, Develop, Disseminate). The conclusion of the development of thematic practicum modules in the Early Childhood Islamic Education Study Program (PIAUD) which was developed through the 4D model has succeeded in producing a valid practicum module.